Ubuntu unleashed - Helmke, Matthew; Hudson, Andrew, 1978-; Hudson, Paul, 1979- (Unleashed, 2019)
Covers 18.04, 18.10, 19.04, and 19.10 Ubuntu Unleashed 2019 Edition is filled with unique and advanced information for everyone who wants to make the most of the Ubuntu Linux operating system. This new edition has been thoroughly updated, including two new chapters, by a long-time Ubuntu community leader to reflect the exciting new Ubuntu 18.04 LTS release, with forthcoming online updates for 18.10, 19.04, and 19.10 when they are released. Linux writer Matthew Helmke covers all you need to know about Ubuntu 18.04 LTS installation, configuration, productivity, multimedia, development, system administration, server operations, networking, virtualization, security, DevOps, and more--including intermediate-to-advanced techniques you won't find in any other book. Helmke presents up-to-the-minute introductions to Ubuntu's key productivity and web development tools, programming languages, hardware support, and more. You'll find new or improved coverage of the Ubuntu desktop experience, common web servers and software stacks, containers like Docker and Kubernetes, as well as a wealth of systems administration information that is stable and valuable over many years. Configure and use the Ubuntu desktop Get started with multimedia and productivity applications, including LibreOffice Manage Linux services, users, and software packages Administer and run Ubuntu from the command line Automate tasks and use shell scripting Provide secure remote access and configure a secure VPN Manage kernels and modules Administer file, print, email, proxy, LDAP, DNS, and HTTP servers (Apache, Nginx, or alternatives) Learn about new options for managing large numbers of servers Work with databases (both SQL and the newest NoSQL alternatives) Get started with virtualization and cloud deployment, including information about containers Learn the basics about popular programming languages including Python, PHP, Perl, and gain an introduction to new alternatives such as Go and Rust